Measuring library anxiety of international students of U.P. Diliman - Mateo, Marc Paul R.; Santos, Yhna Therese P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
According to studies, international students go to the Philippines primariy to study English writing and speaking skills, meet new friends, experience a nes culture, etc. They face many difficulties studying abroad. Aside from cultural adjustments, they also adjust to the new education system, new people, new places, new weather, etc. The library is one of the areas that international students need to adjust. It was discovered that students experience the feeling of being lost and inadequacy during their initial visits to the library. Library anxiety is the term used to describe these feelings experienced by students.
To have an idea about the degree of anxiety that international students experience, a quantitative tool was developed for this study. The library anxiety scale is widely used in different countries as a tool to measure the degree of anxiety. It was also the goal of this research, to measure the degree of library anxiety that the international students of U.P. Diliman experience. All 55 respondents under the category of official cross-registrants, private cross-registrants, and special student participated in answering the library anxiety scale. The respondents were also interviewed to determine the causes of the library anxiety.
Results showed that the top sources of library anxiety come from technological barriers, knowledge of the library, and comfort with the library. In terms of gender, males showed higher levels of anxiety than their female counterpart. In terms of age, younger group of people experience higher level of anxiety. However, older age group showed smaller level of library anxiety. To give better service to the students, the libraries, student organizations and other individuals must collaborate with each other.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) -- Students; Library anxiety -- Philippines -- Quezon City; Library users -- Philippines -- Quezon City -- Psychology; Students, Foreign -- Philippines -- Quezon City